Research on the Low-voltage Distribution and Data Acquisition System ofAutonomous-rail Rapid Tram - CHEN Chaolu; LUO Huang; DONG Qiai; XIE Bin (Kongzhi Yu Xinxi Jishu)
It is difficult to implement load status information monitoring and management issues for low-voltage power distribution system composed of traditional electrical components such as relays and circuit breakers. A network distribution and data acquisition system based on intelligence low-voltage distribution module and CAN/ETH gateway was introduced together with its application through modular, network and integrated design method. Firstly, the composition of network distribution and data acquisition system was introduced. Then, the system architecture and function of the distributed power distribution and data acquisition system based on Ethernet communication and CAN communication were discussed. Finally, the function of data diagnostic information and remote monitoring was described. The network distribution and data acquisition system realizes the intelligence control and information management and improves the intelligence of autonomous-rail rapid tram.